Patent foramen ovale as a rare cause of sudden refractory hypoxemia: a case report - Allaham, Haytham; Bennett, Samuel; Sonbol, Mark; Annabathula, Rahul; Barr, Brian (Frontiers in Cardiovascular Medicine, 2025)
An 80-year-old man presented with progressive dyspnea and severe hypoxemia refractory to high-flow oxygen therapy and was found to have a large persistent patent foramen ovale (PFO)-mediated right-to-left shunt (RTLS). The patient underwent successful percutaneous PFO closure via a 35 mm Amplatzer septal occluder guided by intracardiac echocardiography (ICE), resulting in complete resolution of his hypoxia within 24 h. This case report highlights the workup of systemic refractory hypoxemia, the importance of cardiac shunt physiology in considering an RTLS, and the utility of PFO closure under ICE guidance. For patients with a PFO-mediated RTLS, percutaneous closure is an effective therapeutic option.